An integrated process for removal and recovery of Cr(VI) from electroplating wastewater by ion exchange and reduction–precipitation based on a silica-supported pyridine resin. (1st November 2019) - Ye, Zhenxiong; Yin, Xiangbiao; Chen, Lifeng; He, Xinyi; Lin, Ziming; Liu, Caocong; Ning, Shunyan; Wang, Xinpeng; Wei, Yuezhou
Abstract: Chromium and its compounds are widely used in industry, but Cr(VI) derived from processes such as electroplating is harmful to humans. Thus, it is necessary to remove and recycle Cr(VI) for chromium resource preservation and to prevent toxicity issues. In this study, a facile process that combines ion exchange and reduction–precipitation based on a silica-based pyridine resin is proposed to remove and recover Cr(VI) from electroplating wastewater. A strong-base silica-supported pyridine resin, SiPyR-N4, was firstly employed to selectively remove Cr(VI) through ion exchange. Batch experiment results suggested that SiPyR-N4 could reach sorption equilibrium within 5 min with a 99.3% removal efficiency from a 100 mg/L Cr(VI) solution at a pH of 4, which demonstrates the excellent adsorption kinetics. Furthermore, silica-based resin in a column functions even at a high flow rate of 6 mL/min. By comparison, the Cr(VI) treatment capacity of the D201 resin was less than half that of SiPyR-N4, and the IRA-400 resin was completely disabled under the same conditions. These results demonstrated that ion exchange using SiPyR-N4 is a rapid and efficient approach for Cr(VI) removal. For reduction–precipitation, reductive desorption desorbed 96.67% with a concentration factor of 11.84 at a desorption rate of 2 mL/min, and 98.6% high-purity chromium was recovered by precipitation. Based on these results, a procedure combining ion exchange and reduction–precipitation was employed, which could rapidly remove highly toxic Cr(VI) to protect the environment and effectively recycle chromium resources for sustainable development. In conclusion, the combined process has the potential to recycle Cr(VI) from wastewater on an industrial scale. Graphical abstract: Image 1 Highlights: A facile process was proposed to separate and recover Cr(VI). The silica-supported pyridine resin exhibited excellent adsorption kinetics. Cr(VI) was selectively adsorbed onto the silica-based resin column rapidly. Adsorbed Cr(VI) was efficiently eluted by reductive desorption. High-purity chromium was able to be recovered for reuse.